Effects of Different Ion Erosion on the Hydration Mechanism and Microstructure of Nano-Clay Single-Liquid Grouting Material - Zi-jie Hong; Zi-jie Hong; Jian-ping Zuo; Jian-ping Zuo (Frontiers in Physics, 2022)
The effect of nano-clay (NC) on hydration and microstructure of grouting materials was investigated under different erosion conditions. Six different contents of NC specimens were prepared. This study investigated the effect of NC on the mechanical properties and microstructure of grouting materials under chloride ion erosion and standard curing conditions (SCCs), using ultrasonic pulse velocity (UPV), uniaxial compressive strength (UCS), Fourier transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The experimental results demonstrated that the nano-core effect can promote the formation of the core reaction of grouting materials and accelerate the hydration process. With the NC increase, the hydration products of ettringite (AFt) and calcium silicate hydrate (C-S-H) also increases. Under chloride ion erosion, it was obtained that when NC was less than 2%, the UCS and UPV were improved. As the NC content is 2%, the hydration reaction is the most appropriate. However, under high humidity conditions, as the NC content is 1%, the amount and density of AFt increased and the formation of C-S-H gel enhanced. The hydration reaction inhibited, and the mechanical properties of grouting materials decreased when NC was further increased. It indicated that the complex underground engineering environment affected the hydration mechanism of nano-grouting materials.